Factors Associated with Health Discussion Network Size and Composition Among Elderly Recipients of Long Term Services and Supports - Abbott, Katherine M. (Health Commun, 2012)
Social networks play an important role in helping older adults monitor symptoms and manage chronic conditions. People use verbal discussions to make sense of symptoms, determine their seriousness, and decide whether to seek medical care. In this study, problem-specific social networks called health discussion networks (HDNs) are examined over time among older adults receiving long-term services and supports (LTSS). Data were gathered from older adults who had recently moved into a nursing home (NH) or assisted-living facility (ALF) or who had started to receive home and community-based services (H&CBS). LTSS recipients identified people with whom they discussed symptoms or disease information, talked over what their physician said, and considered consulting other health-care providers. Data were analyzed for 216 adults with Mini Mental State Examination (MMSE) baseline scores of 20 or higher, and these individuals were interviewed quarterly over a 12-month period. Generalized Estimated Equations (GEE) were used to model repeated measures of HDN size and composition as a function of baseline age, gender, race, ethnicity, marital status, education, quality of life, setting, number of adult children, and cognitive status. GEE modeling demonstrated that HDN size decreased over time (p=.01) and that the probability of mentioning formal care providers as part of that network increased over time (p=.003). Multivariate predictors of increased HDN size were lower ratings of quality of life (p=.001), having more adult children (p=.04), and higher MMSE scores (p<.0001) after controlling for covariates. Older adults new to receiving LTSS had relatively small HDNs that were mixed networks including family, friends, and formal care providers. This suggests an opportunity for interventions aimed at maintaining and enhancing the HDNs of older adults beyond family members.